Gender (im)balance in the Russian cinema: on the screen and behind the camera - Xenia Leontyeva; Olessia Koltsova; Deb Verhoeven (Journal of Cultural Analytics)
The relationship between on-screen and off-screen inequality in film industries and the relative impact of these on movie attendance is widely discussed but not necessarily empirically demonstrated. This article examines the binary gender composition of film project teams and the gendered representation of film characters as factors for cinema attendance. We collected a unique dataset (N=1285) of all films released during the pre-pandemic decade (2008-2019) in Russia – at that time the largest European cinema market. A marked-up subset of 243 films was used to calculate a novel version of the Bechdel-Wallace test that accounts for the proportion of all non-stereotypical dialogues in the film narration, as opposed to the classical binary test. Our test proves very informative, revealing a strikingly high proportion of dialogues with stereotypical portrayals of women even among the films that pass the Bechdel-Wallace binary threshold. We also undertook a social network analysis (SNA) of the characters’ communications. This analysis demonstrate that women predominantly occupy a peripheral position in film plots. Both stereotyping and marginalization of women are positively related to the proportion of men in the film crew, especially in the role of screenwriter. Simultaneously, having more men in key positions is also correlated with access to larger budgets and better distribution, thus effectively impeding films with stronger women characters from wider audiences. These audiences, however, show no prejudice towards films with such characters: after 2015, films featuring central women protagonists have the same level of attendance as movies without them. Although Russia exemplifies a large non-Western cinema market, the trends we identify, particularly the “gatekeeping” effect of male filmmakers, is notably in line with those observed in Western democracies.